An exploration into Historical and Political factors for the deviation of the Early Church from Scriptural Principles of Government in Reformed Church perspective - Rev. Dr. Humphreys Frackson Zgambo (Africajournals, 2021)
The question of church government deals with order and authority of the church. The basic principles for sound church polity base on the Scriptural conviction of the Sovereignty of God and Christ as Head and Ruler of the church. The church moved away from this Scriptural principle due to historical and political factors beyond her authority. The study holds that nowhere in the Scriptures do we find an exclusive picture related to any of the fully developed systems of church government today. The New Testament Scriptures suggest a flexible evolving format of plurality of elders in church polity. The aim of the study is to investigate how some ideas and concepts of church government evolved and developed in the history of the church, how historical and political factors forced the church to shift away from principles of Scripture to advocate for a prelacy theory of government practiced over the centuries. In reformed traditional view, the characteristics of hierarchicalism and clericalism in church structures are not accepted. There is no such a thing as highly hierarchical and clerical or ecclesiastical power in the church of Jesus Christ.